2020
DOI: 10.3892/mmr.2020.11448
|View full text |Cite
|
Sign up to set email alerts
|

Astragalin alleviates ischemia/reperfusion‑induced brain injury via suppression of endoplasmic reticulum stress

Abstract: excessive apoptosis and neuronal dysfunction are pathological features of ischemic stroke. Previous studies have demonstrated that astragalin (aST) exerted both antiapoptotic and anti-inflammatory effects in several types of disease, although its potential effect in ischemic stroke remains unclear. The purpose of the present study was to investigate the effects of aST on cerebral ischemia/reperfusion (i/r)-induced brain injury and the underlying mechanisms. Brain injury was assessed in an experimental rat mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…For instance, astragalin, a kind of flavonoid, significantly attenuated the expression levels of apoptotic proteins (Bax and cleaved-caspase-3) and the release of inflammatory cytokines, as well as the ER-related proteins, glucose-regulated protein to alleviate I/R injury via suppression of ER stress on rats after transient middle cerebral artery occlusion (MCAO). Similar results were obtained in vitro neuronal cell culture model ( Liu et al, 2020 ). However, potential contamination, histological techniques, and methodological defects could be encountered in neuron cell culture technology ( Molcanyi et al, 2013 , 2014 ).…”
Section: Introductionsupporting
confidence: 88%
“…For instance, astragalin, a kind of flavonoid, significantly attenuated the expression levels of apoptotic proteins (Bax and cleaved-caspase-3) and the release of inflammatory cytokines, as well as the ER-related proteins, glucose-regulated protein to alleviate I/R injury via suppression of ER stress on rats after transient middle cerebral artery occlusion (MCAO). Similar results were obtained in vitro neuronal cell culture model ( Liu et al, 2020 ). However, potential contamination, histological techniques, and methodological defects could be encountered in neuron cell culture technology ( Molcanyi et al, 2013 , 2014 ).…”
Section: Introductionsupporting
confidence: 88%
“…The current results demonstrated that TMP treatment decreased CHOP and GRP78 expression levels in cells exposed to IL-1β, suggesting a possible mechanism for TMP signaling. To optimize the investigation into the function of ER stress in OA, the present study used TG, which is known to induce ER stress in in vitro models ( 24 ). It was found that TMP exposure markedly decreased TG-triggered ER stress within chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were incubated with TMP (100 µM) ( 22 , 23 ) at 37°C for 24 h in the presence or absence of TG (10 µM) ( 24 ). The concentrations of TMP and TG were mainly selected based on our preliminary experiments and previous reports as aforementioned.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, the exposure of a cell to external or internal stressor stimuli such as chronic hypoxia, low-grade inflammation [ 57 ], and oxidative stress lead to the accumulation of misfolded proteins and cellular damage [ 58 ]. In addition, ER stress can enhance mitochondrial stress and stimulate the apoptosis of the cerebral cells [ 59 ]. Additionally, it has been reported that ER stress is directly proportional to endothelial damage, apoptosis, and dysfunction [ 60 ].…”
Section: Discussionmentioning
confidence: 99%